Effectively remove p-arsanilic acid from water over amphiphilic amino modified collagen fiber. (February 2022) - Ye, Xiaoxia; Lin, Huiting; Chi, Ruiyang; Guo, Zhixuan; Lv, Yuancai; Lin, Chunxiang; Liu, Yifan; Luo, Wei
Abstract: Efficient and rapid removal of p -arsanilic acid ( p -ASA) in water is very important in environmental protection and human health, however it is still a severe challenge in actual engineering. Herein, a novel sorbent (CF-PEI) was successfully fabricated by simply modifying the amphiphilic skin collagen fiber (CF) substrate with Polyethylenimine (PEI). The as-prepared CF-PEI exhibits high-efficiency adsorption for negatively charged p -ASA with aromatic rings due to the introduction of amino groups and the existence of hydrophobic bands, and the maximum adsorption capacity of CF-PEI for p -ASA was high up to 285.71 mg g −1 . In addition, the adsorption mechanism of CF-PEI on p -ASA mainly includes electrostatic interaction, hydrogen bond and amphiphilicity. The multi-level all-fiber structure of CF makes it mainly focus on surface mass transfer with short mass transfer distance, and its capillary drainage effect can realize large flow and rapid separation. CF-PEI based on CF can realize the ability to separate low-concentration p -ASA with high flow rate and high efficiency. The effective processing volume was 12.5 L g −1 when the separation flux reached as high as 9931.27 L m −2 h −1 . Notably, the p -ASA adsorbed on CF-PEI was almost completely eluted by NaOH (0.5 mol L −1 ). The adsorbent is convenient to prepare, recyclable, high in efficiency, and has a great application prospect in removing organic micro-pollutants. Graphical abstract: Image 1 Highlights: A novel amphiphilic adsorbent was prepared from collagen fiber. The negative charge and rigidity of p -ASA enhanced efficient adsorption on CF-PEI. The short mass transfer distance of CF accelerates the mass transfer speed. CF-PEI separated low concentration p -ASA with high flow rate and high efficiency.